The effect of surgical margins on outcomes for low grade MPNSTs and atypical neurofibroma. Issue 7 (11th August 2014) - Bernthal, Nicholas M.; Putnam, Angelica; Jones, Kevin B.; Viskochil, David; Randall, R Lor
<x xml:space="preserve">Abstract</x> Background and Objectives While convention defines atypical neurofibroma as benign and low‐grade malignant peripheral nerve sheath tumors (MPNSTs) as malignant, sparse outcomes data exist for these tumors. This study reviews clinical outcomes of surgically resected low‐grade MPNST and atypical neurofibroma, focusing on the effect of surgical margins on outcome. Methods This study is a retrospective review of 23 patients who underwent surgical resection of a low‐grade MPNST or atypical neurofibroma. Treatment characteristics of adjuvant therapy and surgical margin were noted. Endpoints of local recurrence, presence of metastatic disease, disease‐specific survival, and overall survival were reviewed. Results Eighteen of 23 patients (78%) had microscopically positive margins on the resection. Disease‐specific survival was 100% for both atypical neurofibroma patients and those with low‐grade MPNST, regardless of surgical margin. Local recurrence in terms of recurrence of measureable disease occurred in 2/12 (16.7%) of LGMPNST patients and 1/11 (9.1%) of atypical NF patients, all of whom had microscopically positive surgical margins. Conclusions In a study dedicated exclusively to "intermediate" nerve sheath tumors, no patients developed metastatic disease nor died of disease despite a high rate of microscopically positive surgical margins (78%). While positive margins did lead to increased rates of local recurrence, these data suggest that surgeons potentially can temper their zeal for negative surgical margins in the setting of low‐grade MPNST and atypical neurofibroma, as surgical morbidity may be more important than a presumed survival benefit of wide resection. J. Surg. Oncol. 2014 110:813–816. © 2014 Wiley Periodicals, Inc.